2011
DOI: 10.1111/j.1439-0396.2011.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Inositol hexaphosphate increases mucin loss from the digestive tract of ducks

Abstract: The effects of different forms of inositol hexaphosphate (IP6, phytate) on mucin excretion from the digestive tract of ducks were investigated. Forty-eight ten-wk-old male ducks were grouped by weight into eight blocks of six cages with one bird per cage. On the first day of experimentation, birds received by intubation six dextrose-based diets arranged in a 2 × 3 factorial consisting of phytase (0 or 1000 units) and a form of IP6 (no IP6, free phytic acid or magnesium-potassium phytate). During the 54 h follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The low AID of proline in SE compared to SBM can be explained by NDF and phytic acid concentration in SE, which results in an increased production of mucin in the small intestine (Piel et al., ; Onyango and Adeola, ). Mucin is rich in proline and is poorly digested in the small intestine representing an important proportion of the endogenous protein (Montagne et al., ), reducing AID of proline in SE.…”
Section: Discussionmentioning
confidence: 99%
“…The low AID of proline in SE compared to SBM can be explained by NDF and phytic acid concentration in SE, which results in an increased production of mucin in the small intestine (Piel et al., ; Onyango and Adeola, ). Mucin is rich in proline and is poorly digested in the small intestine representing an important proportion of the endogenous protein (Montagne et al., ), reducing AID of proline in SE.…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acid is a component of some mucins and has been utilized as an indirect measurement of overall mucin production. Dietary phytate has been shown to increase mucin secretion in broiler and duck intestines (Onyango et al 2009;Onyango & Adeola 2012). Pirgozliev et al (2007) reported that 2500 FTU/kg phytase influences endogenous loss including SA from the GIT.…”
Section: Introductionmentioning
confidence: 99%